HPV circulating tumor DNA to monitor the efficacy of anti‐PD‐1 therapy in metastatic squamous cell carcinoma of the anal canal: A case report. Issue 8 (12th July 2017) - Cabel, Luc; Bidard, François‐Clément; Servois, Vincent; Cacheux, Wulfran; Mariani, Pascale; Romano, Emanuela; Minsat, Mathieu; Bieche, Ivan; Farkhondeh, Fereshteh; Jeannot, Emmanuelle; Buecher, Bruno
Abstract : Squamous cell carcinoma of the anal canal (SCCA) is a rare HPV‐associated cancer with limited sensitivity to standard chemotherapy. In a phase 2 study, nivolumab, an anti PD‐1 immune checkpoint inhibitor, demonstrated significant efficacy as single‐agent therapy in metastatic SCCA patients. Nevertheless, imaging assessment by standard RECIST criteria of the efficacy of immune therapy can be difficult in some patients due to tumor immune cell infiltration, and biomarkers of treatment efficacy are needed. We have previously developed a quantitative droplet digital PCR (ddPCR) technique to detect HPV circulating tumor DNA (HPV ctDNA), with excellent sensitivity and specificity. Here, we report, for the first time, the kinetics of HPV ctDNA during therapy in a patient with metastatic SCCA, who obtained sustained partial response to single‐agent nivolumab. We observed an early and very significant decrease of HPV ctDNA during therapy from the baseline level of 3713 copies/ml plasma to 564 copies/ml plasma at 4 weeks, and 156 copies/ml at 6 weeks, followed by a plateau. This observation provides proof‐of‐concept that HPV ctDNA can be used as a noninvasive early dynamic biomarker to monitor the efficacy of new immunotherapy agents. Abstract : What's new? Immune checkpoint inhibitors emerged as a promising strategy against squamous cell carcinoma of the anal tract, a cancer associated with high‐risk human papilloma virus (HPV) infection. However, the radiological evaluation of treatment success is often hampered by tumor pseudo‐progression due to immune infiltration. Here the authors performed synchronous monitoring of blood HPV DNA levels during therapy using droplet‐digital PCR, uncovering the potential of circulating viral DNA as a useful biomarker for treatment success in anal cancer.